2001
DOI: 10.21273/horttech.11.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Ornamental Cabbage and Kale Cultivar Comparison Study: Growth Characteristics and Response to Daminozide and Uniconazole Foliar Sprays

Abstract: Twenty-six ornamental cabbage and kale (Brassica oleracea var. acephala) cultivars were grown in 8-inch (20.8-cm) diameter pots during Fall 1998 to classify their foliage traits and determine their response to the plant growth regulator (PGR) daminozide. Cultivar vigor was classified by height. Foliage characteristics were described and cultivars of ornamental cabbage, notched ornamental kale, and curly ornamental kale were selected for retail or wholesale markets based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…), respectively, to different PGRs at varying concentrations when applied as sprays. Similarly, Boldt (2008), Gibson and Whipker (2001), and Krug et al (2007) reported variation among cultivars of angelonia (Angelonia angustifolia), ornamental cabbage and kale (Brassica oleracea), and tulip (Tulipa gesneriana) in response to different PGRs.…”
mentioning
confidence: 95%
“…), respectively, to different PGRs at varying concentrations when applied as sprays. Similarly, Boldt (2008), Gibson and Whipker (2001), and Krug et al (2007) reported variation among cultivars of angelonia (Angelonia angustifolia), ornamental cabbage and kale (Brassica oleracea), and tulip (Tulipa gesneriana) in response to different PGRs.…”
mentioning
confidence: 95%
“…The 'Coral Prince' cultivar produced higher (54.4 cm on average), more leafy plants (139.3 leaves) than the 'Pigeon Red' cultivar (respectively: 43.4 cm, 88.4 leaves) with a larger rosette diameter. Also, in the study of Gibson and Whipker (2001), 'Coral Prince' formed taller plants with a larger diameter than 'Pigeon Red' (31.6 cm and 40.9 cm vs 27.8 cm and 36.1 cm, respectively).…”
Section: Resultsmentioning
confidence: 92%
“…In 2010, the diameter of the colourful rosettes represented an average of 59.8% of the total, while, in 2011, it was only 30.5% (Table 5). In order to achieve full decorative qualities, the effects of low temperatures should last about 2-3 weeks (Whipker et al 1998;Gibson et al 2001). In September 2011, the average 10-day temperatures were: 15.4, 16.3 and 14.0 °C (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations